answersLogoWhite

0


Best Answer

8x - 7y = 7 (A)7x + 8y = 8 (B)

7*(A): 56x - 49y = 49

8*(B): 56x + 64y = 64


8*(B)-7*(A): (64+49)*y = 64-49

=> 113y = 15

=> y = 15/113


User Avatar

Wiki User

โˆ™ 2015-12-28 20:58:26
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
840 Reviews

Add your answer:

Earn +20 pts
Q: How do I solve for y the linear equations 8x-7y equals 7 and 7x equals 8y equals 8?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked